Consistent warped ℝ × T 1,1 reduction of heterotic supergravity - Liang Ma; H. Lü (Journal of High Energy Physics)
Abstract We find a curious duality between the bosonic sector of heterotic supergravity and the noncritical bosonic string with conformal anomaly. This allows us to map the Mink4 × S 3 × S 3 vacuum of the bosonic string to a new warped ℝ × (T 1,1 × Mink4) vacuum of the heterotic theory, which turns out to be supersymmetric, preserving 1/4 of the supersymmetry. We perform consistent dimensional reduction of the heterotic theory on the warped ℝ × T 1,1 internal space and obtain N $$ \mathcal{N} $$ = 1, D = 4 supergravity, with one complex scalar multiplet and SU(2) × SU(2) Yang-Mills multiplets, where the gauge symmetry is originated from the isometry group of T 1,1.